Law 15/2022, of July 12, on equal treatment and non-discrimination. The inclusion of new autonomous causes of prohibition of discrimination - Grau Pineda , Carmen (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
Nine months have already passed since the approval of Law 15/2022 and, this March, the echoes of the expectations that its approval generated return. We are witnessing the first Spanish law on anti-discrimination law that covers both existing and future discrimination, a law that pursues the double objective of preventing and eradicating any form of discrimination and protecting victims and, therefore, deserves the consideration of law of guarantees, general law, and comprehensive law.Taking as reference the art. 14 CE and, together with the six “classic” grounds for discrimination included in community regulations -birth, racial or ethnic origin, sex, religion, opinion, any other personal or social condition or circumstance-, expressly incorporates those of age, orientation or sexual identity and gender expression, disability, disease or health condition, serological status and/or genetic predisposition to suffer pathologies and disorders, language and socioeconomic situation. This contribution intends to conduct a first approximation to the causes that are presented as most controversial and that, surely, will generate an extensive and lengthy debate, both doctrinal and jurisprudential in the immediate future.
Keywords: Equality; non-discrimination; anti-discrimination law; gender; ageism; disease and disability